2020
DOI: 10.3390/w12102918
|View full text |Cite
|
Sign up to set email alerts
|

Stable-Isotope-Aided Investigation of the Effect of Redox Potential on Nitrous Oxide Emissions as Affected by Water Status and N Fertilization

Abstract: Soils are the dominant source of atmospheric nitrous oxide (N2O), especially agricultural soils that experience both waterlogging and intensive nitrogen fertilization. However, soil heterogeneity and the irregular occurrence of hydrological events hamper the prediction of the temporal and spatial dynamics of N2O production and transport in soils. Because soil moisture influences soil redox potential, and as soil N cycling processes are redox-sensitive, redox potential measurements could help us to better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Our results revealed that there was no significant difference in cumulative N 2 O emissions between RR and DR (Table 2), which may be attributed to the similar annual growth duration (Table 6) and average N 2 O emission flux between the two cropping systems (Figures S1 and S2C,D). In addition, soil moisture has great impacts on nitrification and denitrification associated with N 2 O production [38]. In this study, annual precipitation during rice growth was similar between RR and DR (Table 6).…”
Section: Differences In Ghg Emissions Between Ratoon Rice Cropping Sy...mentioning
confidence: 53%
“…Our results revealed that there was no significant difference in cumulative N 2 O emissions between RR and DR (Table 2), which may be attributed to the similar annual growth duration (Table 6) and average N 2 O emission flux between the two cropping systems (Figures S1 and S2C,D). In addition, soil moisture has great impacts on nitrification and denitrification associated with N 2 O production [38]. In this study, annual precipitation during rice growth was similar between RR and DR (Table 6).…”
Section: Differences In Ghg Emissions Between Ratoon Rice Cropping Sy...mentioning
confidence: 53%
“…The different oxidizing or reducing conditions govern the dynamics of CO 2 , N 2 O, and CH 4 , and significant CH 4 production (methanogenesis) is generally active when soils are under strictly reducing conditions (Yu et al, 2008). Numerous studies investigated relationships between soil water saturation and soil Eh due to the influence of groundwater (Cogger et al, 1992;Comerford et al, 1996;Seybold et al, 2002;Thomas et al, 2009;Vepraskas & Wilding, 1983;Wanzek et al, 2018), water table changes (McDaniel et al, 2001), flooding (Brettar et al, 2002;Rinklebe et al, 2016), and irrigation (Wang et al, 2020). Redox conditions in wetland soils are strongly influenced by groundwater level fluctuations, leading to relatively fast (hourly) spatial and temporal changes of oxic and anoxic conditions and correspondingly to changes in the predominance of processes of the N cycle (i.e., ammonification and nitrification vs. denitrification) (Clément et al, 2002;Reddy et al, 1989).…”
Section: Introductionmentioning
confidence: 99%